Comparative Analysis of Two Mathematical Models of Single Diode Photovoltaic Cells for Extracting PV Parameters Using Levenberg – Marquardt Algorithm - Chahet Youssef; Mimouni Abdelmalek; Bouaichi Abdellatif; El Amraoui Mohamed; El Amrani Aumeur; Bejjit Lahcen (E3S Web of Conferences)
In this present study, two mathematical models derived from the single-diode model of photovoltaic (PV) cells and modules are evaluated. Moreover, the two mathematical approaches are investigated for the reduced single-diode model and the reduced single-diode combined to Lambert W-function model. The Levenberg-Marquardt optimization algorithm is chosen due to its effectiveness in addressing the complex optimization problems encountered in PV cells modeling. The comparative analysis evaluated the accuracy and computational efficiency of the both models for three PV datasets obtained from the literature. The results demonstrated that the combination of the reduced single-diode with Lambert W-function model achieves a minimum RMSE value of 3.1627×10−4, compared to the reduced single-diode model one of 3.2066×10−4.